A Review of Synthetic Cathinone–Related Fatalities From 2017 to 2020. Issue 1 (February 2021) - La Maida, Nunzia; Di Trana, Annagiulia; Giorgetti, Raffaele; Tagliabracci, Adriano; Busardò, Francesco P.; Huestis, Marilyn A.
Abstract : Background: Synthetic cathinones (SCs) are designer analogs of the natural active principle of khat. Since their appearance on the black market in 2003, their popularity has increased annually, and they have become the most seized class of new psychoactive substances reported to the UNODC Early Warning Advisory system. The constant introduction of newly synthesized molecules makes this issue difficult to monitor. The authors reviewed the most recent SC-related fatalities worldwide to highlight new trends of consumption, reporting acute pharmacological and toxicological symptoms, scene investigations, analytical methods, and reported SC concentrations in diverse biological matrices. Methods: A literature search was performed using scientific databases such as PubMed, Scopus, Science Direct, Web of Science, and Research Gate to identify relevant scientific publications from 2017 to 2020. In addition, a search was conducted through the EU EWS. Results: From 2017 to 2020, 31 different SCs were identified in 75 reported fatal intoxications in the literature, alone or in combination with other substances. The most abused SCs were N-ethylpentylone, N-ethylhexedrone, and 4-chloromethcathinone. The EU EWS included less detail on 72 additional SC-related fatalities from 2017 to 2020. Conclusions: New SCs continuously replace older natural and synthetic stimulant drugs, making determining the cause of death difficult. Analytical methods and high-performance mass spectrometry instruments are essential to detect the low concentrations of these potent new SCs. Little data are available on the pharmacology of these new drugs; the evaluation of toxicological antemortem and postmortem findings provides critical data on the drug's pharmacology and toxicology and for the interpretation of new SC cases.